Integrasi Pendidikan Karakter Berbasis Qurani dan Kearifan Lokal Bugis - Yusuf, Yusuf (Jurnal Studi Agama dan Masyarakat, 2015)
This article studies about education character bases on the quranic values and local wisdom, particularly Bugis culture. Conceptually,  the education must be able to build character through internalization of religious values and local wisdom. First, self control by religious approach is to empower religious values as an early prevention to corruption and manipulation. Second, to  empower local wisdom values, in this case Bugis culture, which are relevant to Islamic doctrine. Both culture and Islamic teach universal truths such as honesty, integrity, truth, and goodness. Character education through internalization of core values must be in all education activities, including planning, process, and its evaluation. Integration of cognitive, affective, psychomotor aspects in all education process can build multiple intelligences. Integration of universal values of religion and core values of culture aims at preparing leaders who have  a good character.